Efikasi Antibakteri; Staphylococ pengembangan e-modul mikrobiologi berbasis penelitian pemanfaatan kulit buah kabau sebagai antibakteri untuk meningkatkan keterampilan berpikir kritis mahasiswa - Sitorus, Lizken; Sipriyadi; Nursa’adah, Euis (PendIPA Journal of Science Education, 2025)
The bark of the traditional plant, Archidendron bubalinum, known locally as kabau, exhibits promising qualities as a natural antibacterial agent. This research was conducted with two main objectives: (1) to evaluate the antibacterial efficacy of kabau fruit peel extract against two common pathogenic bacteria, Staphylococcus aureus and Escherichia coli, and (2) to design, validate, and assess the effectiveness of a research-based Microbiology E-Module in fostering students' critical analytical skills. The antibacterial capacity was tested using the paper disc diffusion method across a range of extract concentrations (5%, 10%, 20%, 40%, and 80%), using both pure water (aquades) and 2% dimethyl sulfoxide as carriers. Statistical analysis (one-way ANOVA, p = 0.020 < 0.05) indicated a notable difference in the zone of inhibition diameter across the various concentrations. The most potent antibacterial effect was observed at the 80% concentration with the aquades solvent, yielding inhibition zones of 3.97 mm against S. aureus and 8.42 mm against E. coli. These empirical results served as the core content for the innovative E-Module. The developed E-Module attained a high level of validity, achieving a CVR score of 1.00 from 5 expert validators, thus confirming its readiness for use. Subsequent evaluation during instructional application revealed a marked elevation in students' critical thinking abilities. Students in the Biology Department at FMIPA, Universitas Bengkulu, showed an initial mean pre-test score of 41.67, which surged to 88.00 in the post-test. This change resulted in an N-gain score of 0.79, positioning the improvement in the "high" category. Therefore, A. bubalinum extract is confirmed to hold antibacterial potential, and the E-Module is proven to be an effective educational tool for enhancing students' critical thinking competence.